Dynamics Modeling and Simulation of Gear Transmission System of Shift Mechanism for 4WD Transfer Case - Gao Yangyang; He Feng; Zhang Yongde; Li Jiajun; Guo Chaolun; Huang Wei (Jixie chuandong)
There is a great significance to study the dynamics characteristics of gear transmission system and analyze the vibrational mechanism in the gear transmission of shift mechanism for 4 WD transfer case.Through building the pure torsion dynamics model of the three-stage planetary gears and two-stage cylindrical spur gears,and based on the torsional vibration method,the multi-body dynamics simulation model of the shift mechanism is established on the LMS Virtual. Lab Motion platform. Considering the time-varying meshing stiffness of the internal excitation of the gear,the BDF method is used to solve the problem. The accuracy of the model is verified by comparing the rotational speed of the output shaft obtained by simulation with the theoretical value,and the dynamic meshing force variation curve between the gears is obtained,which can provide dynamic input for further study on the vibration noise of the system.